The relationship between cognitive emotional regulation and impulsivity with the mediating role of executive functions in female students with conduct disorder - Khakzad, Zahra; Moradi, Hojatollah; Bigdeli, Hossein (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Objective: This study aimed to examine the relationship between cognitive emotional regulation and impulsivity, considering the mediating role of executive functions in female students with conduct disorder.Method: The current study was descriptive-correlational predictive research, and in terms of its purpose, it was applied research. The study population comprised all female middle school students in Kermanshah during the 2023-2024 academic year, among whom 200 were selected as the sample using a simple random sampling method. In the field of data collection, both library and field methods were employed. For the field portion, to collect the necessary data, questionnaires were used including Gross and John (2003) Emotion Regulation, Buss and Perry (1992) Impulsivity, and Gioia et al. (2000) Executive Functions Behavioral Rating. Pearson correlation coefficient and regression model analysis in SPSS were used for data analysis.Results: The study results showed that cognitive-emotional regulation affects impulsivity in female students with conduct disorder. Also, executive function affects impulsivity in these students; ultimately, the results indicated that cognitive-emotional regulation impacts impulsivity in female students with conduct disorder, mediated by executive function.Conclusion: These results suggest that interventions aimed at improving cognitive-emotional regulation and executive functions could be effective in managing impulsivity in this population. Further, the study provides valuable insights into the complex interplay between emotional regulation, executive functions, and impulsivity, which can inform future research and practice in psychology and health, particularly in the context of educational settings and adolescent mental health.